Epidermal growth factor receptor‐tyrosine kinase inhibitors in advanced squamous cell carcinoma of the lung: A meta‐analysis. Issue 3 (September 2014) - Ameratunga, Malaka; Pavlakis, Nick; Gebski, Val; Broad, Adam; Khasraw, Mustafa
Abstract Aim Tyrosine kinase inhibitors (TKIs) targeting the epidermal growth factor receptor (EGFR) are well established in treating metastatic pulmonary adenocarcinoma, especially patients with activating EGFR mutations. EGFR mutations are rare in pulmonary squamous cell carcinomas (SCCs). There are conflicting data supporting the efficacy of EGFR‐TKIs in advanced lung SCC. We analyzed the impact of EGFR‐TKIs on progression‐free survival (PFS) and overall survival (OS) in unselected patients with lung SCC. Methods We searched for randomized controlled trials (RCTs) comparing EGFR‐TKIs alone with placebo in patients with metastatic non‐small cell lung cancer. RCTs in all settings (front line/maintenance/subsequent) were included. The primary outcome was OS in the SCC population. We used published hazard ratios (HRs), and when unavailable, unpublished data were sought. Pooled estimates of treatment effect on OS and PFS were calculated using the fixed‐effects inverse variance weighted method. Results Eight eligible RCTs were included: 2 first‐line, 6 second‐line or beyond, evaluating 1781 patients. Data were available for OS in four studies (second‐line; N = 1420) and for PFS in four studies (3 second‐line, 1 first‐line; N = 788). EGFR‐TKIs significantly prolonged OS with a HR of 0.88 (95% confidence interval [CI] 0.78–1.00, P = 0.04), and significantly prolonged PFS with a HR of 0.77 (95% CI 0.65–0.92, P = 0.004). Conclusion EGFR mutations are rare in lung SCC. However, EGFR‐TKIs have a modest therapeutic effect compared to placebo in unselected patients with advanced pulmonary SCC, and can be considered in these patients. EGFR‐mutation‐independent mechanisms may explain efficacy of EGFR inhibitors in this setting.